PENGALAMAN MENGHENTIKAN KEBIASAAN MEROKOK PADA MANTAN PEROKOK - Cicilia Ika Wulandari; Agus Santoso (Jurusan Keperawatan, Universitas Diponegoro, 2012)
Smoking is an unhealthy lifestyle. Effects of smoking not only give the impact to that smokers but also those near the smoker. Quitting smoking requires the support of a healthy conditions. The purpose study to determine the experience of stopping smoking to ex-smokers in the Village of Semarang Tembalang. Qualitative research with a phenomenological approach. Samples carried out with a purposive method, consists of 4 participants. Data collection techniques with in-depth interviews. Result showed that the smokers addicted due to smoking is something that brings pleasure because of the nicotine content. The impact of smoking is a physical disorder, social, economic and psychological. The way to to quit smoking by committing. The kind of support that obtained ex-smokers made up from external, friends and also internal, family.